The genetic basis of metabolic disease - Barroso, Inês (Cell, 2019)
Recent developments in genetics and genomics are providing a detailed and systematic characterisation of the genetic underpinnings of common metabolic diseases and traits, highlighting the inherent complexity within systems for homeostatic control, and the many ways in which that control can fail. The genetic architecture underlying these common metabolic phenotypes is complex, with each trait influenced by hundreds of loci spanning a range of allele frequencies and effect sizes. Here, we review the growing appreciation of this complexity and how this has fostered the implementation of genome-scale approaches that deliver robust mechanistic inference, and unveil new strategies for translational exploitation.